Impact of extraction techniques and processing conditions on pectin and antioxidant recovery from mango peels - Margaret James; Samuel Imathiu; Søren B. Engelsen; Willis Owino (Discover Food)
Abstract The mango processing industry generates peels as byproducts, which are a rich source of bioactive compounds, including pectin. This study aimed to evaluate the impact of extraction methods on antioxidants and pectin yields from mango peels to determine the most effective techniques for recovery of bioactive compounds for potential applications in food industry. The antioxidants were extracted using microwave assisted extraction (MAE), enzyme assisted extraction (EAE), ultrasound assisted extraction (UAE) and water-bath assisted extraction (WBAE) while pectin extraction was performed using MAE, conventional acid extraction (CAE) and UAE. Drying methods (solar, oven, freeze) and mango varieties (Apple, Ngoe) were also analyzed for their influence on pectin yield. Antioxidant analysis revealed similar total phenolic content (TPC) across MAE, UAE, and WBAE, with EAE and UAE showing the highest DPPH scavenging activity (84%). Pectin yield was highest for the CAE method (21.5%; optimal conditions: pH 1.5, 80 °C, 1 h), followed by MAE (19%; pH 1.5, 900 W, 6 min) and UAE (8%; pH 1.5, 40 kHz, 30 min). The degree of esterification (DE) of MAE pectin (54%) was significantly higher than CAE extracted pectin (47%). MAE pectin exhibited a water-holding capacity (WHC) of 7.29 g water/g sample, comparable to 8.05 g for CAE pectin. Significant differences were observed in oil-holding capacity (OHC) and swelling capacity (SWC), with MAE pectin showing higher soluble dietary fiber content and swelling ability. Freeze-drying and the Apple variety gave slightly higher pectin yields than other drying methods and the Ngoe variety, respectively, though the differences were not significant. Fourier-transform infrared (FTIR) spectroscopy confirmed the structural integrity of the extracted pectin, with characteristic hydroxyl (-OH), carbonyl (C = O), and glycosidic (C–O–C) absorption bands. The absence of lipid or wax contamination in all pectin samples confirmed their purity. This study highlights the potential of mango peel pectin in waste valorization aimed for food applications.